2017
DOI: 10.1128/cvi.00556-16
|View full text |Cite
|
Sign up to set email alerts
|

Australian Aboriginal Children with Otitis Media Have Reduced Antibody Titers to Specific Nontypeable Haemophilus influenzae Vaccine Antigens

Abstract: Indigenous populations experience high rates of otitis media (OM), with increased chronicity and severity, compared to those experienced by their nonindigenous counterparts. Data on immune responses to otopathogenic bacteria in these high-risk populations are lacking. Nontypeable Haemophilus influenzae (NTHi) is the predominant otopathogen in Australia. No vaccines are currently licensed to target NTHi; however, protein D (PD) from NTHi is included as a carrier protein in the 10-valent pneumococcal polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…[38][39][40] Moreover, they found that Australian aboriginal (possibly similar to OP) children with otitis media displayed lower serum IgG to NTHi but not Spn proteins than non-aboriginal (possibly similar to NOP) or healthy children. [41] Consistent with our findings, these observations also suggest that OP children in different geographic areas may have similar defects in producing serum antibodies to certain otopathogens. The full linear model is log 2 (Y i j ) = log 10 (A i j ) × COL i j × OP i + u i + e i j , i = 1, …, n, j = 1, …, n i , (1) where log 10 (A ij ) × COL ij × OP i includes all main effects and interactions, u i is a subject level random effect and e ij is the remaining error term.…”
Section: Discussionsupporting
confidence: 91%
“…[38][39][40] Moreover, they found that Australian aboriginal (possibly similar to OP) children with otitis media displayed lower serum IgG to NTHi but not Spn proteins than non-aboriginal (possibly similar to NOP) or healthy children. [41] Consistent with our findings, these observations also suggest that OP children in different geographic areas may have similar defects in producing serum antibodies to certain otopathogens. The full linear model is log 2 (Y i j ) = log 10 (A i j ) × COL i j × OP i + u i + e i j , i = 1, …, n, j = 1, …, n i , (1) where log 10 (A ij ) × COL ij × OP i includes all main effects and interactions, u i is a subject level random effect and e ij is the remaining error term.…”
Section: Discussionsupporting
confidence: 91%
“…We have also observed that Aboriginal otitis-prone children have similar natural antibody titres to pneumococcal protein antigens when compared with their non-Aboriginal counterparts [39]. Aboriginal otitis-prone children did, however, have lower natural antibody titres to specific NTHi protein antigens [40], indicating that Aboriginal children may be tolerised to NTHi from a young age and cease responding to some NTHi antigens. It is possible that the different ethnic groups within the PCV10 group have different antibody responses to Protein D, but this had no impact on density of NTHi (or pneumococcal) colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with those of other research pertaining to Indigenous children's health showing high rates of dental conditions, inadequate access to dental care 5 and high rates of chronic ear infections. [40][41][42][43][44] Lower percentages of visits to ear-and throat-related specialists among the First Nations cohort compared with the non-First Nation cohort was an unexpected result considering the higher percentage of diagnoses for related conditions.…”
Section: Discussionmentioning
confidence: 99%